Survival rate of pulpectomy in primary teeth using Feapex® paste: a clinical study in infants - Abanto, Jenny; Olegário, Isabel; Mendes, Fausto; Bönecker, Marcelo; Corrêa, Maria Salete (Brazilian Dental Science, 2021)
Objective: The aim of this clinical study was to evaluate the survival rate of a new pulpectomy protocol using 2% chlorhexidine digluconate gel and Feapex paste for endodontic treatment in primary teeth. Material and Methods: A total of 105 pulpectomies were performed in anterior and posterior teeth of 48 infants (1-3 years old) with high caries experience with irreversible pulpitis or pulp necrosis. All treatments were performed by dental surgeons with no specialization in Pediatric Dentistry, under local anesthesia and rubberdam isolation. Manual files were used in conjunction with 2% chlorherixidine gel for root canal instrumentation, and Feapex® paste was used as a obturation material. The clinical and radiographic outcomes were collected by one trained independent evaluator with a follow-up period of 24months. Success was determined by the absence of pain, pathological mobility, pathologic bone rarefaction, pathological root resorption and soft tissue pathology around the affected tooth Survival of the endodontic treatment was evaluated by estimating survival rates through Kaplan-Meier curves. Cox Regression analysis with shared fragility were performed to evaluate the association between the independent variables to endodontic treatment failure (alpha=5%). Results: After 24 months, the treatment survival was 86% (SE=0.03). Root resorption at baseline was associated with a higher risk of failure (HR=2.81; CI=1.12-7.08; p=0.027). The survival rate of the endodontic treated teeth due to dental trauma was 100%, while teeth with dental caries had lower survival rate (85.05%; p<0.001*). Other variables analyzed included gender, age of the child, tooth position (incisor/molar), restoration type, obturation quality, and caries experience were not associated with treatment failure (p>0.05). Conclusion: The new protocol using 2% chlorhexidine digluconate and Feapex® presented a high survival rate and can be considered as a suitable protocol for pulpectomy in primary teeth.Trial Registration: REBEC (RBR-282s2f). KEYWORDS Root canal treatment; Primary teeth; Infants; Pulpectomy.